Pemberian Edukasi Pentingnya Sayuran Bagi Siswa TK Kartika Untuk Meningkatkan Minat Makan Sayur - Ridanies, Yustina Adventia (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Consuming enough vegetables for young children, especially children at kindergarten level, is important to meet their nutritional needs, namely a minimum of five portions in seven days. The main content contained in vegetables is high dietary fiber which is very important for the growth of early childhood. Low consumption of vegetables in early childhood is a problem that often occurs in the environment around us, so there is a need for socialization regarding this matter. The method for this socialization is through lectures and demonstrations using poster media. This socialization activity was carried out on October 3 2023 at TK Kartika 3-17 which is located at Jl. Tobong No. 2 Tuguran, Potronson, District. North Magelang, Magelang City, Central Java. The target of this activity is kindergarten students in classes A and B, with 20 students in class A each, and 19 students in class B.